66 Simple Rules for Entrepreneurs - Shepherd, Dean A.; Patzelt, Holger; Breugst, Nicola (Springer Nature, 2024)
This open access book is your ticket to entrepreneurial success! Learn practical tips to think more like an entrepreneur, spot opportunities, build key relationships, tell compelling stories, and grow your venture. Discover the secrets to overcoming challenges, managing stress, and making decisions in the dynamic world of entrepreneurship. Whether you're a seasoned entrepreneur or just starting, these straightforward tools will guide you to success in the complex entrepreneurial landscape. Say goodbye to overwhelming decisions and hello to a simplified path to building your entrepreneurial dream!